2019
DOI: 10.1177/2167696819867533
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Adults’ Public and Private Discussions of Substance Use on Social Media

Abstract: Substance use increases during emerging adulthood and may relate to higher concurrent and future problems. For a community sample of 140 emerging adults, this study explores the associations between reported alcohol, marijuana, and tobacco use in 12th grade, the content of public posts and private messaging on Facebook during the fall after 12th grade, and self-reported substance use 1 year after high school. About one quarter of participants discussed substances publicly, and nearly half discussed substances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
(25 reference statements)
0
13
1
Order By: Relevance
“…We have also shown that counts of alcohol-related words in sent and received private text messages are associated with higher odds of same-day drinking (Jensen & Hussong, 2019). Longitudinal research suggests that these associations may be bidirectional, with those youth who had previously been using substances being more likely to evidence later public and private substance-related discussions, and public and private conversations predicting later increases in marijuana use (but not alcohol or tobacco use; George et al, 2019). Taken together, these findings highlight the importance of future research that attends to how private digital communication channels may be uniquely indicative of substance use risk.…”
Section: Alcohol-and Drug-related Posting and Substance Use Behaviorsmentioning
confidence: 60%
See 2 more Smart Citations
“…We have also shown that counts of alcohol-related words in sent and received private text messages are associated with higher odds of same-day drinking (Jensen & Hussong, 2019). Longitudinal research suggests that these associations may be bidirectional, with those youth who had previously been using substances being more likely to evidence later public and private substance-related discussions, and public and private conversations predicting later increases in marijuana use (but not alcohol or tobacco use; George et al, 2019). Taken together, these findings highlight the importance of future research that attends to how private digital communication channels may be uniquely indicative of substance use risk.…”
Section: Alcohol-and Drug-related Posting and Substance Use Behaviorsmentioning
confidence: 60%
“…Qualitative coding of real, naturalistic text message data has revealed that most of these teens engaged in at least some antisocial text messaging, and that this text messaging about antisocial activities was associated with increases in multiple reporters' accounts of rule-breaking behavior (Ehrenreich et al, 2014). Furthermore, findings suggest that the reason for associations between peer network delinquent texting topics and youth externalizing problems might be better characterized as selection (externalizing adolescents choosing deviant peer groups) rather than socialization (deviant peer groups driving externalizing behavior; Ehrenreich et al, 2019).…”
Section: Online Depictions Of Offline Delinquencymentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of social media content are also promising and perhaps more feasible given the practical constraints on observing text messaging content. We have previously examined markers of affect and social support on Facebook (Ehrenreich & Underwood, 2016), as well as private and public discussions of substance use on Facebook (George et al, 2019). Other studies have coded social media content, including indices of self-presentation (e.g., Butkowski et al, 2019;Rodriguez & Hernandez, 2018); selfies (e.g., Barry et al, 2019); substance use (e.g., Beullens & Schepers, 2013); and markers of self-disclosure, aggression, and deviancy (Khalis & Mikami, 2018).…”
Section: Moving the Field Forward With More Sophisticated Methodsmentioning
confidence: 99%
“…While shaping their narrative identity, the boundless nature of social media provides emerging adults with a developmental window of opportunity for growth and deepened development, but also leaves them vulnerable to risk and maladaptive behaviours (Coyne et al, 2013;. For example, social media can complement real-world relationships by providing additional mechanisms for meeting people, keeping in touch, and experiencing perceived social support, but can also detract from real-life relationships and result in poorer relationship quality, communication problems, and increased jealousy (Coyne et al, 2013).Involvement in social media platforms can be associated with pathological media use, anxiety, depressive symptoms, alcohol consumption, drug use, and diminished academic performance (Coyne et al, 2013;George et al, 2021;Vannucci et al, 2019;Walsh et al, 2013). In contrast to this, researchers have also found evidence of how social comparisons on social network sites can be a form of inspiration and elicit positive motivational outcomes conducive to well-being (Meier et al, 2020;Noon & Meier, 2019).…”
Section: The Interplay Between Social Media and Identitymentioning
confidence: 99%